Design Techniques for Mash Continuous-Time Delta-Sigma Modulators - Liu, Qiyuan (Springer International Publishing, 2018)
This book describes a circuit architecture for converting real analog signals into a digital format, suitable for digital signal processors. This architecture, referred to as multi-stage noise-shaping (MASH) Continuous-Time Sigma-Delta Modulators (CT-ΔΣM), has the potential to provide better digital data quality and achieve better data rate conversion with lower power consumption. The authors not only cover MASH continuous-time sigma delta modulator fundamentals, but also provide a literature review that will allow students, professors, and professionals to catch up on the latest developments in related technology.